2015
DOI: 10.1007/s12264-015-1533-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-controlled matrix metalloproteinase-9 hyperexpression promotes behavioral recovery after ischemia

Abstract: Matrix metalloproteinase-9 (MMP-9) plays a benefi cial role in the sub-acute phase after ischemic stroke. However, unrestrained MMP-9 may disrupt the blood-brain barrier (BBB), which has limited its use for the treatment of brain ischemia. In the present study, we constructed lentivirus mediated hypoxiacontrolled MMP-9 expression and explored its role after stroke. Hypoxia response element (HRE) was used to confine MMP-9 expression only to the hypoxic region of mouse brain after 120-min transient middle cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…This vector made it possible to use MMP-9 to treat brain ischemia. 9 Our results showed that the brain atrophy volume was reduced and neurological function was improved when injecting HRE-MMP-9 into the peri-infarct area 7 days after tMCAO. On the basis of previous studies, MMP-9 had detrimental effects, including BBB disruption, inflammation, and neurotoxicity in the acute phase of stroke (the first 3 days), but it could help to mediate repair in the late stage of ischemia (7-14 days).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…This vector made it possible to use MMP-9 to treat brain ischemia. 9 Our results showed that the brain atrophy volume was reduced and neurological function was improved when injecting HRE-MMP-9 into the peri-infarct area 7 days after tMCAO. On the basis of previous studies, MMP-9 had detrimental effects, including BBB disruption, inflammation, and neurotoxicity in the acute phase of stroke (the first 3 days), but it could help to mediate repair in the late stage of ischemia (7-14 days).…”
Section: Discussionmentioning
confidence: 49%
“…7,8 Our previous study showed that the hypoxiainducible factor (HIF)-1a-hypoxia response element (HRE) system could successfully control MMP-9 expression, and HRE-MMP-9 overexpression in the ischemic mouse brain promoted behavioral recovery. 9 However, the therapeutic mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SB-3CT blocks MMP9 activity through an irreversible covalent interaction (Jia et al, 2014; Sassoli et al, 2014). Mice were treated with 10 mg/kg SB-3CT daily starting 24 hours prior to injury in combination with MMP9-specific collagen matrix injections (Cai et al, 2015). Auf1 KO mice treated with SB-3CT showed near complete extinction of MMP9 activity at the site of IP injection and significantly reduced MMP9 activity in the injured TA muscle (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Ischemic stroke is one of the main causes of mortality and disability worldwide [1]. During ischemic stroke, the blockage of cerebral blood flow leads to brain damage and neuronal death through a series of pathological mechanisms including endoplasmic reticulum (ER) stress.…”
Section: Introductionmentioning
confidence: 99%